Filsafat Etika Tasawuf Syaikh ‘Abdul Qadir Al-Jailani: Kajian Etika Salik dalam Kitab Ghunyat li Thalibi Thariq al-Haqq - Aly Mashar; Nailal Muna (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This brief paper wishes to examine the ethical concept of Sufism Shaykh Abdul Qadir al-Jailani in the book Ghunyat li Thalibi Thariq al-Haqq, especially the ethics of Sufism of a salik found in the last part of the book. This paper is classified as library research with analysis using the perspective of ethical philosophy. Sufism values remain in the corridors of the Qur'an and Sunnah, the soul is clean from impulse, always bound and happy with Allah, maintain harmony, emphasize respect and an attitude of compassion, and not be the cause of others hurt. If observed in terms of the source of truth that always measures with the source of texts, both the Qur'an, the sunnah of the prophet, friends, tabi'ain and the saints, then it can be said that the ethics of Sufism Shaykh Abdul Qadir al-Jailani belong to theological ethics. However, if seen from the emphasis on the priority of people rather than the salik, then it falls into the category of ethical altruism.